Peranan dan Analisis Faktor Produksi Subsektor Bahan Galian Golongan C di Indonesia: Estimasi Regresi Panel Data Makro - Anggraini, I Gusti Ayu Puspita; Wahyuni, Krismanti Tri (Seminar Nasional Official Statistics, 2024)
The production results of the mining and other quarrying subsectors are often called class C excavations and are mostly used by other sectors as raw materials. The importance of class C excavation for other sectors makes it necessary to increase production output. Production results can be increased by using a combination of inputs that can be seen with the production function. Therefore, this research aims to look at the role and potential of class C minerals, analyze the general description of production and production functions and analyze the stats that influence output. The analytical method used is the panel data regression method with the SUR approach. The research results show that there are 18 provinces with mining and other quarrying subsectors classified as basic or superior. Production output and production factors appear to fluctuate. Variables that influence output were analyzed using the SUR method panel data regression model and it was found that labor, capital and technology had a positive and significant effect on production results, while fuel had a negative and significant effect.